Predictive value of blood routine-derived inflammation indexes for varicella-zoster virus meningitis in patients with acute herpes zoster - Zhang, Yan; Yuan, Yanrong; Liu, Huili; Wang, Jun; Yan, Yongxing (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBlood routine-derived inflammation indexes have been studied in many diseases. However, their roles in varicella-zoster virus (VZV)-related central nervous system (CNS) infection diseases are unclear. This study analyzed the value of blood routine-derived inflammatory indexes in the diagnosis and prognosis of VZV meningitis in patients with acute herpes zoster (HZ).MethodsA total of 31 cases of VZV meningitis were selected as the research subjects, with 64 cases of acute HZ admitted to our hospital during the same period as the control group. The blood routine markers and blood routine-derived inflammatory indexes were compared between the two groups. Univariate analysis, logistic regression, and receiver operating characteristic (ROC) curve analysis were used to evaluate the correlation between the levels of each inflammatory marker and the occurrence of VZV meningitis, as well as to evaluate the relationship between the inflammatory markers and the prognosis of VZV meningitis at discharge.ResultsCompared with those in the HZ group, the patients in the VZV meningitis group showed significantly increased platelet-to-lymphocyte ratios (PLRs), neutrophil-to-lymphocyte ratios (NLRs), and systemic immune-inflammation index (SII) scores (p < 0.05 and p < 0.01), while the absolute counts of lymphocytes decreased (p < 0.05). Multivariate logistic regression analysis showed a correlation between the PLR and the occurrence of VZV meningitis. The PLR also showed a significant correlation with the prognosis of VZV meningitis patients at discharge (r = 0.774, p < 0.01).ConclusionThe PLR, as a potential inflammatory index, may have certain clinical value in predicting the occurrence and prognosis of VZV meningitis.